Dominant Water Quality Variables Affecting Plankton Abundance in Traditional Brackish Water Ponds of Tiger Shrimp (penaeus monodon fabr.) in Pasuruan Regency, East Java Province - Erfan Andi Hendrajat; Andi Sahrijanna (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
ABSTRACTIn applying traditional brackish water pond aquaculture of tiger shrimp (Penaeus monodon), plankton is one of water micro organisms that plays an important role as natural food and stability indicator of water or aquatic environment in which life and growth of aquatic organisms depend on water quality variables, both physical and chemical properties. This research objective was to find out the effects of dominant water variables on plankton abundance in brackish-water pond. The research was conducted in traditional brackish water ponds of tiger shrimp in Pasuruan Regency, East Java Province. The research was conducted through direct measurements in the field and also collection of plankton and water samples. Those were then analyzed in the laboratory. Better change to analysis used in this study was regression model analysis was based on the smallest square method. Dependent variables was plankton abundance and independent variables were the water quality variables such as temperature, dissolved oxygen, salinity, pH, total suspended solid (TSS), nitrite, nitrate, ammonia, phosphate, iron (Fe), and total organic matter (TOM). The result showed that range of plankton abundance was 20.0-6,360 individuals/L with average 401.3 individuals/L. There was a significant relationship between plankton abundance and TSS which negatively affected plankton abundance as much as 0.52 or 52%. Based on index values of average dominance, variety, and uniformity, the brackish water pond water or aquatic area in this study was categorized as moderately stable, where plankton genera were well distributed and there was no genus dominating other genus.